Effect of late prophylaxis in hemophilia on joint status: a randomized trial. (10th October 2017) - Manco‐Johnson, M. J.; Lundin, B.; Funk, S.; Peterfy, C.; Raunig, D.; Werk, M.; Kempton, C. L.; Reding, M. T.; Goranov, S.; Gercheva, L.; Rusen, L.; Uscatescu, V.; et al.
Abstract : Essentials High‐quality data are lacking on use of prophylaxis in adults with hemophilia and arthropathy. SPINART was a 3‐year randomized clinical trial of late/tertiary prophylaxis vs on‐demand therapy. Prophylaxis improved function, quality of life, activity and pain but not joint structure by MRI. Prophylaxis improves function but must start before joint bleeding onset to prevent arthropathy. Summary: Background: Limited data exist on the impact of prophylaxis on adults with severe hemophilia A and pre‐existing joint disease. Objectives: To describe 3‐year bleeding, joint health and structure, health‐related quality‐of‐life (HRQoL) and other outcomes from the open‐label, randomized, multinational SPINART study. Patients/Methods: Males aged 12–50 years with severe hemophilia A, ≥ 150 factor VIII exposure days, no inhibitors and no prophylaxis for > 12 consecutive months in the past 5 years were randomized to sucrose‐formulated recombinant FVIII prophylaxis or on‐demand therapy (OD). Data collected included total and joint bleeding events (BEs), joint structure (magnetic resonance imaging [MRI]), joint health (Colorado Adult Joint Assessment Scale [CAJAS]), HRQoL, pain, healthcare resource utilization (HRU), activity, and treatment satisfaction. Results: Following 3 years of prophylaxis, adults maintained excellent adherence, with a 94% reduction in BEs despite severe pre‐existing arthropathy; 35.7% and 76.2% of prophylaxis participants were bleed‐free or had fewer than two BEs per year, respectively. As compared with OD, prophylaxis was associated with improved CAJAS scores (least squares [LS] mean, − 0.31 [ n = 42] versus + 0.63 [ n = 42]) and HAEMO‐QoL‐A scores (LS mean, + 3.98 [ n = 41] versus − 6.00 [ n = 42]), less chronic pain (50% decrease), and approximately two‐fold less HRU; activity, Euro QoL‐5D‐3L (EQ‐5D‐3L) scores and satisfaction scores also favored prophylaxis. However, MRI score changes were not different for prophylaxis versus OD (LS mean, + 0.79 [ n = 41] versus + 0.96 [ n = 38]). Conclusions: Over a period of 3 years, prophylaxis versus OD in adults with severe hemophilia A and arthropathy led to decreased bleeding, pain, and HRU, better joint health, activity, satisfaction, and HRQoL, but no reduction in structural arthropathy progression, suggesting that pre‐existing joint arthropathy may be irreversible.